Atuação docente com estudantes surdos nos anos iniciais do ensino fundamental - Paulo, Joeliton Francisco Sousa de (2019)
The theme of deaf education has been frequently debated in the field of Cultural Studies of Education, focusing on the process of schooling of these students in basic education. In this paper, we seek to analyze how the listening teachers had been conducting the education of deaf students in the early years of elementary school in the city of Pedras de Fogo-PB. The locus of investigation were 02 (two) regular schools of the municipal network, and participated in this research 02 (two) listening teachers. To carry out the investigation, a qualitative research with a methodological approach based on content analysis was used, using semi-structured interviews as the technique for data collection. In the data analysis three main categories were extracted: conceptions about deaf being, educational approach and bilingual education. The analysis revealed the unpreparedness of teachers to work with deaf students in the classroom, showing that they see their deaf students only for disability, based on a medical-therapeutic model, and do not use any educational approach in the classroom. The research highlights the current need to review teacher education, thinking strategies for an education that offers recognition of cultural, identity and linguistic aspects of deaf students.